SOCICIAL INSTITUTIONS AS SUBJECTS OF SOCIO-PHILOSOPHICAL ANALYSIS - Литовченко, І. В. (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2014)
This article treating concepts of the genesis of social institutions and by their socio-philosophical analysis. Substantiates the part and place of social institutions as a key element in the social structure.